A LINGUOCULTURAL AND POETIC ANALYSIS OF TRANSLATION STRATEGIES IN RENDERING NAVOI’S GHAZALS (International journal of artificial intelligence, 2026)
This study examines the translation of Alisher Navoi’s ghazal (No. 16) through a comparative analysis of its Russian, English, and Korean versions. The research focuses on the preservation and transformation of key poetic features, including meter (aruz), rhyme, radif, phonetic organization, and stylistic devices. Employing the method of objective analysis and a linguocultural approach, the study evaluates how different translators render both the semantic content and aesthetic value of the original text.The findings demonstrate that each translation reflects a distinct strategy: some prioritize semantic accuracy, while others emphasize formal and rhythmic equivalence. The analysis reveals that the reproduction of poetic form, particularly elements such as rhythm, sound patterns, and structural organization remains one of the most challenging aspects of ghazal translation. At the same time, the study highlights the importance of considering cultural and pragmatic factors in achieving stylistic adequacy.Overall, the paper argues that poetic translation is not merely a process of linguistic transfer but a creative interpretative act shaped by the interaction of linguistic, cultural, and aesthetic dimensions. The results contribute to the broader field of translation studies by providing insights into the complexities of translating classical Eastern poetry across different languages and poetic systems.